2021
DOI: 10.2169/internalmedicine.6816-20
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ankle Brachial Index with Clinical Outcomes Following Percutaneous Coronary Intervention in Patients with Aortic Aneurysm

Abstract: Objective Since patients with thoracic aortic aneurysm (TAA)/abdominal aortic aneurysm (AAA) are often complicated with coronary artery disease, it is common for those patients to undergo percutaneous coronary intervention (PCI). The ankle brachial index (ABI) is usually measured in patients with TAA/AAA to screen the presence of peripheral arterial disease. The present study investigated the association between the ABI and clinical outcomes following PCI in patients with TAA/AAA. Methods and Material We divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…An abnormal ABI has been linked to atherosclerosis severity and adverse cardiovascular outcomes. 22 In our study, we also found that a lower ABI predicts the occurrence of VC. Operators need to pay close attention during procedure when they have abnormal ABIs.…”
Section: Discussionsupporting
confidence: 72%
“…An abnormal ABI has been linked to atherosclerosis severity and adverse cardiovascular outcomes. 22 In our study, we also found that a lower ABI predicts the occurrence of VC. Operators need to pay close attention during procedure when they have abnormal ABIs.…”
Section: Discussionsupporting
confidence: 72%